Parental Satisfaction with the Care of Admitted Children in a Tertiary Level Hospital - Pandey, Kabita; Shrestha, Sanjana; Shrestha, Sarala (Journal of Nepal Paediatric Society, 2023)
Introduction: The quality care is an essential aspect of hospital service in improving health outcomes. Quality of children’s care can be assessed by measuring the parental satisfaction. Methods: A descriptive cross-sectional design was used. Non-probability purposive sampling was used to select 167 parents of children who were admitted in Kanti Children Hospital. Data were collected by interviewing either the father or mother as roomed-in by using the Pediatric family satisfaction questionnaire (PFSQ) containing three domains as modified to suit to local context. Data were entered, cleaned and analyzed in statistical package for the social sciences SPSS version 22. Chi-square test and Spearman rank correlation coefficient were used to analyze the data. Results: Findings revealed that the overall satisfaction among majority (59.9%) of the respondents was low. However, domain wise, almost all (94.6%) respondents were satisfied in medical care followed by 89.2% in nursing care and lowest proportion (42.5%) was satisfied with hospital services and accommodation. Parental overall satisfaction was significantly higher among those admitted in surgical unit (p = 0.00) and among those with days of hospitalization as more than 6 days (p = 0.01). Findings also showed a moderate correlation between the satisfaction with nursing care and medical care (r = 0.64). Conclusions: Parents tend to have low satisfaction with the care provided to the admitted children whereas domain wise satisfaction is high in medical and nursing care and low in hospital services. Therefore, in order to increases the parental satisfaction, more focus should be given to improve the quality of hospital services and accommodation.